EMERGENCE AGITATION IN PATIENTS WITH POSTTRAUMATIC STRESS DISORDER - LITERATURE REVIEW - Julia Kaszucka; Jakub Jędrychowski; Natalia Karpowicz; Kinga Kosiec-Stolarek; Oliwia Krzemień; Małgorzata Krzyżanowska; Iga Kwiecień; Natalia Pacocha; Agnieszka Raczyńska; Marta Zgierska (International Journal of Innovative Technologies in Social Science, 2025)
Emergence agitation (EA) is an acute condition, characterised by confusion, and restlessness, occurring in the early recovery phase from general anaesthesia. EA can have significant clinical impact, including patient distress, injury, increased morbidity, and increased healthcare costs, as well as possible long-term consequences. Though the pathophysiology of emergence agitation remains unknown, it is believed to involve a multifactorial mechanism, including heightened sympathetic nervous system activation, and psychological factors such as posttraumatic stress disorder (PTSD). PTSD, a psychiatric disorder resulting from exposure to trauma, may predispose individuals to emergence agitation. This literature review aims to examine the relationship between EA and PTSD, highlighting possible mechanisms, prevalence and risk factors involved, as well as discuss possible prevention methods and pharmacological interventions. A comprehensive understanding of the pathophysiology and risk factors of emergence agitation in PTSD patients is critical for developing suitable prevention and anaesthesia management strategies.